2014
DOI: 10.1534/genetics.113.159780
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RNAi Contributes to the Silencing of Off-Target Genes and Repetitive Sequences in Caenorhabditis elegans

Abstract: Small RNAs recognize, bind, and regulate other complementary cellular RNAs. The introduction of small RNAs to eukaryotic cells frequently results in unintended silencing of related, but not identical, RNAs: a process termed off-target gene silencing. Off-target gene silencing is one of the major concerns during the application of small RNA-based technologies for gene discovery and the treatment of human disease. Off-target gene silencing is commonly thought to be due to inherent biochemical limitations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…Accordingly, we did not find strongly enriched gene ontology terms for the targets defined in the oxidized and TAP‐treated libraries (Table EV1). Furthermore, consistent with a role for GTSF‐1 upstream of NRDE‐3, we observed a significant overlap between GTSF‐1‐dependent sRNA targets and NRDE‐3 targets (Zhou et al , ; Fig EV4B).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Accordingly, we did not find strongly enriched gene ontology terms for the targets defined in the oxidized and TAP‐treated libraries (Table EV1). Furthermore, consistent with a role for GTSF‐1 upstream of NRDE‐3, we observed a significant overlap between GTSF‐1‐dependent sRNA targets and NRDE‐3 targets (Zhou et al , ; Fig EV4B).…”
Section: Resultssupporting
confidence: 84%
“… AVenn diagram showing overlap between the 1% FDR GTSF‐1 targets defined in the three different NGS library preparation conditions. BVenn diagram depicting the overlap between the GTSF‐1 targets defined in the oxidized and TAP‐treated libraries in this study, and NRDE‐3 targets as defined elsewhere (Zhou et al , ). C–EExemplary UCSC genome browser tracks with RPM‐normalized sRNA coverage profiles. Three biological replicates of wild‐type N2 worms (Rep. 1–Rep.…”
Section: Resultsmentioning
confidence: 77%
“…Accordingly, we did not find strongly enriched gene ontology terms for the targets defined in the oxidized and TAP-treated libraries (Table S1). Furthermore, consistent with a role for GTSF-1 upstream of NRDE-3, we observed a significant overlap between GTSF-1-dependent sRNA targets and NRDE-3 targets (Zhou et al, 2014) (Figure S4B).…”
Section: G-rna Levels Are Strongly Reduced In Gtsf-1 Mutantssupporting
confidence: 82%
“…The effect on 275 overall bulk 22G RNA levels was only minor ( Figure S2A). Also when we split the 22G RNAs into previously defined sub-categories (Almeida et al, 2019a;Bagijn et al, 2012;Conine et al, 2013;Gu et al, 2009;Phillips et al, 2014;Zhou et al, 2014), we only identified relatively small differences in all pathways analysed ( Figure S2C).…”
Section: Pid-2 Affects Endogenous 22g and 26g Rna Populationsmentioning
confidence: 82%